2019
DOI: 10.1039/c8cc08962k
|View full text |Cite
|
Sign up to set email alerts
|

Iridium and a Brønsted acid cooperatively catalyzed chemodivergent and stereoselective reactions of vinyl benzoxazinones with azlactones

Abstract: Under cooperative catalysis of iridium and a Brønsted acid, different C4-substituted azlactones react with vinyl benzoxazinones via a formal [4+2] cycloaddition or substitution reaction in a chemo- and stereoselective mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 55 publications
0
24
0
1
Order By: Relevance
“…It was found that the utilization of the newly exploited chiral P,S-ligand and hydrogen bonding is the key to control the regioselectivity for this reaction. Apart from palladium catalysis, iridium/Brønsted acid co-catalytic system was applied for the preparation of quinolinones through a formal [4 + 2] cycloaddition by the Shi group [15]. Later, the same group developed a palladium-catalyzed cascade cyclization reaction of para-quinone methides and cyclic carbamates [16].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the utilization of the newly exploited chiral P,S-ligand and hydrogen bonding is the key to control the regioselectivity for this reaction. Apart from palladium catalysis, iridium/Brønsted acid co-catalytic system was applied for the preparation of quinolinones through a formal [4 + 2] cycloaddition by the Shi group [15]. Later, the same group developed a palladium-catalyzed cascade cyclization reaction of para-quinone methides and cyclic carbamates [16].…”
Section: Introductionmentioning
confidence: 99%
“…In case of ligands PCy 3 and dppp, both of them gave 3 aa in the same chemical yields (entries 3 vs. 4). In contrast with the former cases, the chemical yield of the [4 + 2] cycloaddition differently increased with the use of ligands dppb and dppf (entries 1-4 vs. [5][6]. Finally, we found that ligand PPh 3 worked most efficiently among all the checked ligands, and furnished product 3 aa in the highest chemical yield (entry 7).…”
Section: Updatesmentioning
confidence: 70%
“…2). Very recently, the research groups of Mukherjee and Shi separately disclosed the [4+2] cycloadditions of ethynyl‐ or vinyl‐substituted benzoxazinones with oxazol‐5‐(4 H )‐ones. Basically, the N ‐Ts substituent in the vinyl benzoxazinone scaffolds functions as the key structural requirement for the above‐mentioned elegant chemical transformations.…”
Section: Methodsmentioning
confidence: 99%
“…Another important contribution concerning the preparation of dihydrocoumarin scaffolds (48) cycloaddition reactions between o-hydroxylstyrenes (44), which acts as oxa-diene precursors, and azlactones (45) through a cooperative catalysis approach; simultaneously employing a Brønsted acid catalysis (46) and Brønsted base catalysis (47) (Scheme 13). [34] The matched couple between chiral phosphoric acid and chiral guanidine catalysts on the substrates activation was the highlight of this work.…”
Section: Münchnone-based Cycloadditionsmentioning
confidence: 99%
“…Recently, Shi and co-workers described a cooperative catalysis methodology, employing a iridium complex and a Brønsted acid, in the formal [4+2] cycloadditions between vinyl benzoxazinones (86) and azlactones (87), leading to 3,4-dihydroquinolin-2-one (88) in good to excellent yields (ranging from Scheme [44] During the reaction optimization, the authors observed that the use of iridium complex catalyst was superior to most approaches towards vinyl benzoxazinanones using palladium-based catalysts. Moreover, different substituted vinyl benzoxazinones (89) and 2-substituted azlactones (90 and 91) were well tolerated in the optimized reaction conditions.…”
Section: Münchnone-based Cycloadditionsmentioning
confidence: 99%